DISTINCTIVE CUSTOMER-ORIENTED BEHAVIORS: A LITERATURE REVIEW (European Journal of Interdisciplinary Research and Development, 2024)
The research aims to identify the role of distinguished behaviors and how to achieve customer-oriented performance or customer-oriented behavior, as customer service-oriented companies focus on customers and meeting all their needs. Orienting yourself to customer service requires understanding the characteristics and development of customer service skills, and creating a plan that includes actionable steps to do so can help you improve these very important skills. It is essentially a conceptual study of a strategic nature, and calls on researchers to follow the empirical path to validate the identified model and expand the scope of internal marketing and customer-oriented behavior. In this article, we discuss the definition and characteristics of customer service focus and how they can be used to develop these skills further. Differentiating behaviors enhance employee customer-oriented behaviors, as manifested in enjoyment and needs. As hypothesized, authentic emotions partially mediate the effects of differentiation behaviors on customer-oriented behaviors. Theoretical and managerial implications associated with the above findings are discussed. Which indicates that positive customer-oriented behaviors among nurses are linked to increased organizational citizenship behaviors. This means that when nurses have a positive attitude toward clients, they usually display citizen behavior that promotes cooperation and active participation in the organization.